Pemetaan Bawah Permukaan Intrusi Diorit Menggunakan Metode Gravitasi, Magnetik dan AMT di Jiwo Barat, Bayat, Klaten, Jawa Tengah - , D. Arief ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
In Jiwo Barat, Bayat there is a lithological surface contact between metamorph, the oldest rock in Java and Paleogene Limestone. The subsurface contact hasn't yet discovered. There are controversies about the subsurface contact, some considered it as stratigraphy contact and others as structure contact. Magnetic, Gravity, and AMT data measurements are taken simultaneously in figuring out the subsurface of Jiwo Barat area. Magnetic data are used to identify magnetic field anomaly under lithological contact. From gravity modeling we found subsurface rocks density, by AMT method we collect resistivity value of subsurface rocks. Those three kinds of data will provide a detail description about the anomaly. Magnetic field cross section show high gradient anomaly, 110-112 nT at the northern side of surface of lithological contact between metamorphic and limestone. Otherwise, low anomaly (64-70 nT) was revealed at southern part. There is diorite intrusion shown by Gravity modeling with density 2.95 gr/cm3. AMT data provide resistivity value 10 - 4686 o.m, describing that there is diorite in the subsurface.